Establishment of an Ex Situ Collection of Glycyrrhiza glabra L. as a Prerequisite for Field Cultivation in Bulgaria - Asya Kozhuharova; Milena Nikolova; Stoyan Stoyanov; Elina Yankova-Tsvetkova; Vladimir Ilinkin; Strahil Berkov; Marina Stanilova (Horticulturae, 2024)
Glycyrrhiza glabra L. (Fabaceae), commonly known as licorice, is a perennial medicinal plant. Its healing properties are due mainly to the secondary metabolites glycyrrhizin and flavonoids accumulated in the roots of plants aged 3 years or more. Overexploitation of licorice populations in Bulgaria led to their rapid decrease. The species is protected by the national Biodiversity Act. The present study aimed at establishing of an ex situ collection of G. glabra using plant material originating from its Bulgarian populations in order to evaluate the main characteristics of the cultivated plants and their potential use as a source of plant material for the creation of a plantation. Plants were obtained from stolon cuttings of donor wild-growing plants from three Bulgarian populations and then cultivated for 3 years in the experimental field plot. Plants originating from all three populations produced glycyrrhizin and flavonoids in similar concentrations under the controlled conditions of the ex situ collection, despite the significant inter-population differences noted in situ. The soil type and supply of soil organic matter, total nitrogen and other nutrients turned out to be most important for the quality of plants in terms of both their growth and biosynthetic capacity. In addition, in vitro micropropagation has proven to be a suitable method for accelerating seedling production. These results would be of practical importance in establishing an agricultural plantation of G. glabra.